Marketing Practices Legislation And The Concept Of Unfairness Towards Consumers - Harland, David (Journal of Malaysian and Comparative Law, 1993)
An adequate legal framework defining the standard to be observed in the marketplace and setting out the basic rights (and responsibilities) of consumers must be cornerstone of consumer policy. In the absence, for example, of legislation prohibiting misleading advertising effective legal action to prohibit such advertising will scarcely be possible, for provisions of the ordinary criminal law and civil law have usually been found to be quite unsuited to regulate such conduct in any but the most blatant cases.